Behavioural and psychosocial sequelae of severe closed head injury and regional cerebral blood flow: a SPECT study. Issue 6 (June 1992) - Oder, W; Goldenberg, G; Spatt, J; Podreka, I; Binder, H; Deecke, L
Abstract : Thirty six patients (31 male, 5 female) who had suffered severe closed head injury were re-examined at an average of 39.3 (SD 12.8, range 7-66) months after the injury. Behavioural symptoms were measured using the Giessen test. The relatives' reports were used for data analysis to ensure that results were valid. The neurophysical impairment subscale of the Glasgow assessment schedule was completed by two neurologists, and the number connection test was completed by each patient. The adjective mood scale was completed by each relative. All patients were investigated by single photon emission computerised tomography (SPECT). Exploratory factor analysis using the principal components method was carried out separately for SPECT results and psychological measures and correlations were sought between the resulting factors. Factor analysis of the data from the Giessen test identified social isolation, disinhibition, and aggressive behaviour as major components of post-traumatic personality changes; it indicates that these behavioural features are independent of the level of neurological and neuropsychological impairment, which loaded on a single independent factor. Relatives' psychic health seemed to be relatively resistant to physical and cognitive disability and was mainly affected by disinhibitive behaviour. The highest correlation was between frontal flow indices and disinhibitive behaviour (p less than 0.01): the severity of disinhibition increased with lower frontal flow rates. There was a significant but somewhat weaker correlation (p less than 0.05) between flow indices of the left cerebral hemisphere and social isolation. Low flow values of the right brain regions were related to aggressive behaviour (p less than 0.05). Neurological and cognitive impairment correlated negatively with the thalamus; worse neurological and cognitive performance indicate by raised scores on the neurophysical scale and on the number connection test was associated with low thalamic flow values. The results support the importance of lesion location in the production of post traumatic behavioural disorders.